Ocalić od zapomnienia. Melancholia inteligenta w prozie tzw. rozrachunków inteligenckich (1946–1948) - Izabela Kozłowska (Przestrzenie Teorii)
The article deals with the so-called “literature of retribution”, produced between 1946–1948. Postwar literary criticism accused intellectual characters of passivity, self-centeredness and reserve towards contemporary socio-political transformations. The only issue perceived by critics was the attempt to establish the role of the intelligentsia in times of historic breakthrough. My article shows that this way of interpreting the literature of retribution is insufficient. It becomes obvious that the interpretative key used by the literary critics of the 1940s was Marxist ideology, and that their conclusions narrow the scope of the issues touched upon in these novels. These literary works do not only relate the experiences of one social class – they deal with universal issues, those connected with human existence in general and the relationship between the individual, society and the world. The category I use to extract the universal issues from the literary works analysed here is melancholy. The use of the melancholic perspective enriched the traditional interpretation of the “literature of retribution” by lending it a new context and allowing the rehabilitation of the intellectuals it portrayed.